Early Algebraization A Global Dialogue from Multiple Perspectives - Cai, Jinfa; Knuth, Eric.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
In recent years there has been increased interest in the development of students$1 (Balgebraic thinking in the elementary and middle school grades. This important and timely new volume contains the most comprehensive collection of research focused on early algebraization. The volume$1 (Bs authors$1 (Bleading international mathematics education scholars$1 (Bpresent perspectives on early algebraization that promote a global dialogue on the topic. Research is presented from many parts of the world, including Asia, Australasia, Western and Eastern Europe, and North America. The volume authors consider issues concerning early algebraization from three fundamental perspectives$1 (Bcurricular, cognitive, and instructional. The chapters in this volume not only represent the state of the art about research on early algebraization, but also provide suggestions for future research. (3z(BThis volume on early algebraization reveals the rich diversity that characterizes the rapidly evolving field of early algebra .$1! = (Bthis volume offers to researchers, teachers, curriculum developers, professional development educators, and policy makers alike some of the most recent thinking in the field.(3y (B(Carolyn Kieran).s
Series Foreword. SECTION 1: Introduction. SECTION 2 -- Curricular Perspective -- SECTION 3. Cognitive Perspective -- SECTION 4. Instructional Perspective -- SECTION 5. Perspectives for Research and Teaching.
Keywords: Education; International education; Comparative education; Curriculums (Courses of study).; Education -- Curricula; Mathematics -- Study and teaching; Teaching; Education; Mathematics Education; Teaching and Teacher Education; Learning & Instruction; International and Comparative Education; Curriculum Studies; Electronic books